The Metacognitive Learning Instruction (MLI) for Teaching Listening During the Pandemic: Pros and Cons - Titis Sulistyowati; Januarius Mujiyanto; Dwi Rukmini; Rudi Hartono (International Conference on Science, Education, and Technology, 2021)
The purpose of this study is to describe the Metacognitive Learning Instruction (MLI) online classroom application along with its advantages and challenges, which teachers may consider so that they can prepare detailed planning before teaching. This study is part of more extensive experimental research, which is done to study the students' listening achievements and their factors. This paper also presents statistical data analyzing the effect of the MLI on students' listening proficiency. To explain the advantages and disadvantages of using the instruction, the researchers analyze the students’ self-evaluation questionnaires and the instructor's self-reflection questionnaire. Furthermore, this research is carried out to discover the effectiveness of MLI for teaching listening. Paired Sample T-test is performed to test the hypothesis. The test is required to prepare a comparison analysis between pre-test and post-test scores of the same groups. From the paired t-test sample, the researchers report a significant difference between the pre and post-test data. It indicates that the students' listening proficiency increases significantly. Online learning by adopting MLI within blended Synchronous and Asynchronous learning enable students to access the learning materials, ask questions, and practice their skills at any time that works for them. However, teachers need to closely monitor the students' learning progress to assist the students to become independent learners and efficiently use the time allocation to finish the task on time.